ARABIC- BINARIES SYNTAX IN SURAH AL RAHMAN - lubna Farah (دی اسکالر)
This paper study aims to analyze binaries words phenomena in Arabic with a specific focus on Quran e.g “sura Rehman” the Binarity is the pattern of creation, existence the relation between the creator and pairs words, its event of Rhetoric of Quran, dark and light, night and day, life and hereafter. The conflict between man and devil and the fall of Adam from heaven the conflict between Adam sons, the study is an epistemological model based on the binary reality that leads to a monotheistic perspective. The study ponders on Quran and investigates its consolidated epistemology and methodology. The epistemology model is grounded on binary reality which leads to a universal monotheistic perspective. The research paper discusses the central binaries in the Quran and analysis the most important methodological characteristics, such as structural, integration, overlapping, and aesthetic juxtaposition. The research design of this paper is descriptive qualitative, the results of the study show that binaries have a semantic aspects that are of great value in understanding the Quranic texts, a trait that only Quranic texts contain.